Speech Act Pluralism in Argumentative Polylogues - Lewinski, Marcin (Informal Logic)

(untitled) (Informal Logic, 2021)
I challenge two key assumptions of speech act theory, as applied to argumentation: illocutionary monism, grounded in the idea each utterance has only one (primary) illocutionary force, and the dyadic reduction, which models interaction as a dyadic affair between only two agents (speaker-hearer, proponentopponent). I show how major contributions to speech act inspired study of argumentation adhere to these assumptions even as illocutionary pluralism in argumentative polylogues is a significant empirical fact in need of theoretical attention. I demonstrate this with two examples where arguers interacting with multiple persons convey plural, argumentatively relevant illocutionary forces. Understanding illocutionary pluralism in argumentative polylogues also affords a better account of fallacious and manipulative discourse.